Transcriptional response to combination antiretroviral therapy predicts side effects and novel targets - Lachmann, Alexander; Amadori, Letizia; Nicoletti, Paola; Crane, Heidi M.; Giannarelli, Chiara; Ma’ayan, Avi; Peter, Inga (Frontiers in Pharmacology, 2026)
BackgroundAntiretroviral therapy (ART) has revolutionized the clinical management of people with human immunodeficiency virus (HIV), transforming HIV infection into a chronic condition. Yet, the mechanisms of action and off-target effects of modern combination ART regimens versus individual ART medications are not fully understood.MethodsUsing the L1000 assay, we profiled transcriptional responses to 11 single ART drugs and 6 ART combination regimens across three human cell lines, HepPG2 (liver), HK2 (kidney), and THP-1 (monocyte). Differentially expressed genes were analyzed against host-HIV protein-protein interactions (PPIs) and genes implicated in ART-associated side effects.ResultsAcross all cell types, ART combination regimens induced distinct transcriptional profiles compared with their component drugs. Combinations more strongly perturbed genes encoding proteins involved in HIV–host PPIs, consistent with their enhanced antiviral efficacy. Transcriptional responses also recapitulated known ART-induced adverse effects related to dyslipidemia, altered body composition, and renal impairment. Combination regimens were less coupled to these gene signatures, suggesting mechanisms that may underlie their improved safety profiles. Several genes and pathways were consistently modulated across treatments: ACTG1, or actin gamma 1 — a gene that encodes gamma actin, a protein crucial for the localization of the HIV reverse transcription complex, was downregulated in four combination regimens, while ORM2, Orosomucoid 2, upregulation emerged as a common response to individual drugs. ACTG1 was previously found to be downregulated in ART naïve people living with HIV who naturally control HIV replication, suggesting its role as a candidate host mediator. To facilitate data exploration, we developed ARTexpress, an interactive portal enabling visualization of gene expression changes before and after ART exposure across all three cell lines.ConclusionART regimens affected transcriptional signatures of genes involved in HIV-host PPIs and were less tied to common ART-related side effects. Our findings support the use of high-throughput transcriptomics to detect specific mechanisms of ART on- and off-target effects to help prioritize new drug targets and compounds in future development and optimization of safer and more efficient ART.